KAJIAN KUALITATIF PERILAKU PEMBAYARAN ONLINE PADA GENERASI Z DI KOTA MALANG - Farahdisya, Naffisa Nur Zahra; Khusnul Ashar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study was conducted to determine the opinions of the Z generation community regarding the existence of online payments, to determine the effectiveness, satisfaction, and shortcomings felt when using online payments. Through a phenomenology qualitative approach and content analysis method, this study was conducted by interviewing 10 people who are included in the Z generation group in Malang City. The results of the study showed that the majority of informants gave a positive response to the existence of online payments. With online payments, they feel helped and at the same time make it easier when making transactions. Payments when using online payments are much faster and feel more effective when compared to payments using money. However, the results of interviews with informants also found negative experiences felt when using online payments, such as sudden loss of balance, failed transactions, and errors in online payment applications. The effectiveness of online payments will be felt when transactions run properly, supported by cashless services that are available anywhere and a stable internet network. However, the use of online payments still has disadvantages, such as admin fees that can be burdensome and application features that are sometimes unclear.